PENGARUH TOTAL ASSET TURN OVER (TATO) DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN ON ASSET (ROA) PADA PT UNILEVER TBK PERIODE 2012-2024 - Zahrotun Nabilah; Iman Lubis (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of Total Asset Turn Over (TATO) and Sales Growth on Return on Assets (ROA) at PT Unilever Tbk during the 2012–2024 period. ROA is used as an indicator of profitability, TATO reflects asset utilization efficiency, while sales growth indicates the company’s revenue performance over time. The research method employed is a quantitative approach using secondary data from the company’s annual financial reports. Data analysis was conducted using multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results show that TATO has no significant effect on ROA, while sales growth has a significant effect on ROA. Simultaneously, both TATO and sales growth influence ROA. These findings suggest that sales growth plays a crucial role in improving profitability, while asset efficiency alone is not sufficient without adequate sales performance.